1988
DOI: 10.1073/pnas.85.2.477
|View full text |Cite
|
Sign up to set email alerts
|

Neoplastic transformation of mouse mammary epithelial cells by in vitro exposure to N-methyl-N-nitrosourea.

Abstract: High-efficiency neoplastic transformation of mouse mammary epithelial cells in primary collagen gel culture was induced by N-methyl-N-nitrosourea (MNU). Mammary epithelial cells, isolated from virgin BALB/c mice, were embedded within collagen gels and grown in a serum-free medium containing prolactin, progesterone, and linoleic acid.The cells were then treated with MNU on day 3 of culture and subsequently at weekly intervals for up to 4 weeks. Eleven to 14 days after the final carcinogen treatment, the cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…Miyamoto et al reported tumor formation after mammary epithelial cells were exposed to NMU in vitro and injected into cleared fat pads (Miyamoto et al, 1988). These authors used a cell inoculum one order of magnitude higher than the one we used and a different cell purification method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Miyamoto et al reported tumor formation after mammary epithelial cells were exposed to NMU in vitro and injected into cleared fat pads (Miyamoto et al, 1988). These authors used a cell inoculum one order of magnitude higher than the one we used and a different cell purification method.…”
Section: Discussionmentioning
confidence: 99%
“…Non-epithelial cells were successfully removed by treating the plates with a 0.025% trypsin and 0.01% EDTA solution. Five days before being transplanted into recipient animals, the mammary epithelial cells were treated with SFM containing either vehicle or 50 µg/ml NMU for 1 hour at 37°C (Miyamoto et al, 1988). The cells were then rinsed twice with SFM and fresh SFM was added.…”
Section: Mammary Epithelial Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…Another widely used experimental system to study mammary tumorigenesis is the model in which tumors were induced in the Fischer 344 rats by a single dose of N-nitrosomethylurea (NMU) (35,36). On the other hand, Miyamoto et al (37) observed neoplastic transformation of mouse mammary epithelial cells by in vitro exposure to NMU. Furthermore, the highest number of tumors per animal induced by DMBA was observed when the carcinogen was given to animals when they were 40 to 46 days of age, a period when terminal end buds were most actively differentiating into alveolar buds (38).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro model systems have been extensively used to study the processes of initiation, progression and metastasis. Several authors have developed models to study these processes (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Most of them give a unique opportunity for studying mammary gland changes that can occur by the effect of different exogenous and endogenous substances.…”
Section: Introductionmentioning
confidence: 99%